Aggressive operative neurosurgical management in patients with extra-axial mass lesion and Glasgow Coma Scale of 3 is associated with survival benefit: A propensity matched analysis. Issue 1 (January 2016) - Salottolo, Kristin; Carrick, Matthew; Levy, A. Stewart; Morgan, Brent C.; Mains, Charles W.; Slone, Denetta S.; Bar-Or, David
Abstract: Introduction: Prognosis in patients with traumatic brain injury (TBI) and Glasgow Coma Scale (GCS) score of 3 is poor, raising concern regarding the utility of aggressive operative neurosurgical management. Our purpose was to describe outcomes in a propensity matched population with TBI and GCS3 treated with operative neurosurgical procedures of craniotomy or craniectomy (CRANI). Methods: We conducted a five-year, multicenter retrospective cohort study of patients with an ED GCS 3 and a positive head CT identified by ICD-9CM diagnosis codes. Two populations were examined: (1) patients with extra-axial mass lesion (subdural or epidural haematoma), (2) patients without mass lesion (subarachnoid and intraparenchymal haemorrhage including contusion, other intracerebral haemorrhage or intracranial injury including diffuse axonal injury). In patients with extra-axial mass lesion, propensity score techniques were used to match patients 1:1 by CRANI, and the following outcomes were analysed with conditional logistic regression: survival, favourable hospital disposition to home or rehabilitation, and development of complications. Results: There were 541 patients with TBI and GCS3; 19% had a CRANI, 83% were initiated within 4 h. In those with mass lesion, 27% (91/338) had a CRANI; after matching, a significant survival benefit was observed with CRANI vs. without CRANI (65% vs. 34% survival, OR: 3.9 (1.6–10.5) p < 0.001). There was borderline increased odds of favourable disposition (43% vs. 26%, OR: 2.4 (0.99–6.3, p = 0.052) with CRANI vs. without CRANI, and no difference in developing a complication (58% vs. 48%, OR: 1.5 (0.7–3.4), p = 0.30). Conclusions: Survival was achieved in 65% of patients that underwent surgical intervention for subdural and epidural haematoma, despite a presenting GCS of 3. These results demonstrate prompt operative neurosurgical management of mass lesion is warranted for selected patients with a GCS of 3, contributing to a significant 4-fold survival benefit. In the absence of mass lesion the effect of immediate neurosurgery on outcomes is inconclusive.